Het Vlaamse standpunt en de socialistische partij. - Van Eynde, Jos (Leuven Hilversum : Nauwelaerts Paul Brand, 1963)
Bibliotheek Camille Huysmans
Overdruk uit: 'De Maand', nr. 5, 1963
Nederlands
Monografie